Anti-Anxiety Effects of Essential Oil Microemulsion in Chronic Unpredictable Mild Stress-Induced Rats: Preparation, Characterization, and Mechanisms - Tang, Wenxia; Jiang, Pan; Hu, Ke; Mei, Duo; Jiao, Qinghao; Li, Yan; Deng, Yanping; Wang, Jun; Gao, Ran; Chen, Xin; Yu, Jie (Molecules (Basel, Switzerland), 2025)
Anxiety disorders, as common neurological diseases in clinical practice, often coexist with depression. Epidemiological surveys indicate that approximately 85% of patients with depression exhibit significant anxiety symptoms. This comorbid state not only exacerbates clinical symptoms but also leads to treatment resistance and prolonged disease duration. This study innovatively developed a compound aromatic plant essential oil (EO) formulation with remarkable anxiolytic and antidepressant effects and systematically elucidated its mechanism of action. The study found that the essential oil formulation, administered via inhalation, could significantly improve behavioral abnormalities in animals subjected to the chronic unpredictable mild stress (CUMS) model, specifically manifesting as (1) the reversal of stress-induced weight gain retardation; (2) a significant increase in sucrose preference; (3) an increase in the total distance of spontaneous activity; and (4) the prolongation of exploration time in the open arms of the elevated plus maze. Neuropathological examinations confirmed that the formulation could effectively protect the structural integrity of hippocampal neurons and alleviate CUMS-induced neural damage. In terms of mechanism of action, the study revealed that the formulation regulates the neurotransmitter system through multiple targets: (1) the upregulation of serotonin (5-HT) and γ-aminobutyric acid (GABA) levels; (2) the downregulation of glutamate (GLU) concentration; and (3) key targets identified via network pharmacological analysis, such as ESR1, STAT3, and PPARG. These findings provide molecular-level evidence for understanding the neuromodulatory effects of aromatic essential oils. Pharmaceutical formulation studies showed that the oil-in-water (O/W) type compound essential oil microemulsion, prepared using microemulsification technology, has a uniform particle size and excellent stability, maintaining stable physicochemical properties at room temperature for an extended period, thus laying a foundation for its clinical application. This study not only validates the practical value of traditional medicine but also provides new ideas for the development of novel anxiolytic and antidepressant drugs, achieving an organic integration of traditional experience and modern technology.